Implementasi Komunikasi Efektif dalam Peningkatan Keselamatan Pasien - Sulistyowati, Arlina Dhian; Kusumaningrum, Puput Risti (JUKEJ : Jurnal Kesehatan Jompa, 2026)
Patient safety was an important indicator of health service quality and was strongly influenced by the effectiveness of communication among health professionals. Ineffective communication could lead to medical errors and decreased quality of care. This study aimed to determine the relationship between effective communication and patient safety at PKU Muhammadiyah Prambanan Hospital. This research used a quantitative method with a correlational design. The sample consisted of 16 nurses selected using purposive sampling techniques. The instruments used were effective communication and patient safety questionnaires. Data were analyzed using the Spearman’s rho test. The results showed that the majority of respondents were female (93.8%), held a diploma in nursing (87.5%), and had less than one year of work experience (56.2%). The level of effective communication among nurses was high (87.5%), and the level of patient safety was also high (75%). The Spearman’s rho test results indicated a strong and significant relationship between effective communication and patient safety with a correlation coefficient of r = 0.764 and p = 0.001 (p < 0.05). It was concluded that the better the communication performed by nurses, the higher the implementation of patient safety. It was recommended that the hospital improve training in effective communication using the SBAR (Situation, Background, Assessment, Recommendation) method to minimize information errors and strengthen the culture of patient safety.